A Linear Relationship between Fitness and the Logarithm of the Critical Bottleneck Size in Vesicular Stomatitis Virus Populations - Novella, Isabel S. (American Society for Microbiology (ASM), 2008)
We explored the relationship between fitness change and population size during transmission in vesicular stomatitis populations of very high fitness. The results show a linear correlation between the logarithm of the critical bottleneck size (population size at which there are no significant fitness changes after 20 passages) and the initial fitness of the population. In addition, limits to fitness increases during large-population passages of very-high-fitness strains were abolished by increasing the population size during transmission, indicating that beneficial variation is still available in these populations.